DEVELOPMENT AND EVALUATION OF CLOBETASOL PROPIONATE NANOEMULGEL WITH BABCHI OIL FOR FUNGAL INFECTIONS - Sarita Karole, Kailendra Malgaya, Nidhi Prakashkumar Shah, Kavita Shukla, Reema Singh, Sudipta Roy, Rakesh Singh, Prof. Archana Shaha (South Eastern European Journal of Public Health, 2025)
Fungal infections pose significant dermatological challenges, necessitating the development of effective topical therapies with enhanced permeability and minimal side effects. Clobetasol propionate (CP), a potent corticosteroid, is commonly used to manage inflammatory skin conditions but is associated with poor skin permeability and systemic side effects.“This study focuses on the development and evaluation of a CP-loaded nanoemulgel incorporating babchi oil (Psoralea corylifolia) to enhance antifungal efficacy. The nanoemulsion was formulated using the aqueous phase titration method, with babchi oil as the oil phase, Tween 80 as the surfactant, Transcutol P as the co-surfactant, and distilled water as the aqueous phase. The optimized nanoemulsion (NE14) was incorporated into a hydroxypropyl methylcellulose (HPMC) gel base to improve viscosity and enhance patient compliance. The formulation was characterized for physicochemical properties, in vitro drug release, skin permeability, antifungal activity, and stability. The optimized nanoemulgel exhibited a globule size of 236.67 nm, zeta potential of -20 mV, pH of 6.29, and viscosity of 4438.69 cP. In vitro permeation studies showed 97.59% cumulative drug release over 24 hours, demonstrating sustained release. The antifungal activity, assessed using the agar well diffusion method against Candida albicans and Trichophyton rubrum, revealed a 35% larger zone of inhibition compared to a marketed CP gel, confirming enhanced antifungal potential. The study concludes that CP-loaded nanoemulgel with babchi oil offers a stable, effective, and patient-friendly alternative for treating fungal infections, warranting further clinical investigation.”